Developing Computer-Based Instructional Media for English Speaking Skill at Senior High School - Rohmah, Farida Noor (JET (Journal of English Teaching), 2019)
This research aimed at developing computer-based instructional media using Adobe Flash for the tenth graders’English speaking skill material. The studyemployed research and development method. The results showed (1) the product is a computer-based instructional media in a combined format of tutorial and drilling facilitating semiinteractive learning consisting of thanking, complimenting, congratulating, surprise and disbelief materials; (2) the expert validation showed that the product quality in terms of media is categorized very good (4.51) and in terms of the material and instructionalare categorized good (3.91). The results of the field trials showed that the quality of the product in terms of material, media, and instructional is categorized very good (4.32). In conclusion, the developed media is eligible to be implemented in speaking learning activities. Keywords: computer-based instructional media; Adobe Flash; speaking skill